Review of Important Aspects and Performances of Polymer Flooding versus ASP Flooding - Sagyndikov, M.S.; Kushekov, R.M.; Seright, R.S. (KU Publ., 2022)
Polymer flooding is a promising and effective chemical Enhanced Oil Recovery (cEOR) technology. Polymer flooding is especially cost-effective, whereas other chemical flooding methods, such as Alkaline Surfactant Polymer (ASP), are not profitable and cause serious on-site problems (scaling, uptime decrease, injectivity issue, hard-breaking emulsions). Recent papers in the literature mention ~30 field polymer floods. Most of them reported technical success. Although, polymer flooding has been applied ~60 years and it still requires further investigation to provide improvements. Thus, this paper describes important aspects and performances during polymer flooding based on a review of recent projects, combined with the Kalamkas field experience. A comprehensive literature review examines the applicability range in temperature, brine salinity, water source selection, oil properties, formation type, and permeability. Water source selection has an essential role during pilot/field project design and is one of the most responsible technical and economic success decisions. Polymer slug design has been extensively analyzed especially for the high viscosity oil fields; the selected oil/polymer viscosity ratio was usually much less than one. We placed significant emphasis on clarifying observed high polymer injectivities. We conducted feasibility studies of some reported ASP floods to clarify that this technology is not profitable at current oil prices. Also, we performed TAN analysis of three Kazakhstan oil fields for screening of ASP flood.
ASP суландырумен салыстырғандағы полимерлерлі суландыруының маңызды аспектілері мен нәтижелеріне шолу
Обзор важных аспектов и характеристик полимерного заводнения в сравнении с ASP заводнением
Keywords: polyacrylamide; polymer flood; chemical enhanced oil recovery (EOR); alkaline surfactant polymer (ASP); feasibility study